Fuzzy-AHP approach for performance measurement in shrimp agroindustry - Lely Herlina; Yanyan Dwiyanti (Journal Industrial Servicess, 2021)
Performance measurement is needed by industry, including the food processing industry. One of the food processing industries is shrimp agroindustry. Performance measurement for shrimp agroindustry is necessary because of competition from similar industries. Performance measurement can be used as a basis for making strategies in decision-making systems. It is one way the shrimp agroindustry survives in market competition. This study aims to determine the performance matrix in the shrimp agroindustry. Fuzzy-AHP is used to design performance measurements. The results of the performance matrix are as follows: efficiency (0.268), quality (0.226), flexibility (0.061), responsiveness (0.120), coordination and collaboration (0.085) and sustainability (0.239).